Implicações da infecção por Leishmania amazonensis em modelos de diabetes mellitus induzido - Andrade, Nayhane Caroline (2019)
Leishmaniasis is caused by different protozoan species of the gender Leishmania and their interaction with the host's immune system results in a broad spectrum of clinical and immunopathological presentations. Diabetes mellitus (DM) may adversely affect th e immune response, leading to increased susceptibility to infections. Immunomodulators such as β -glucans (BG) have been used in the control of blood glucose and in parasitic infections. Considering the scarcity of studies evaluating the course of leishmaniasis infections correlated to DM, in addition to the use of Saccharomyces cerevisiae BG in this infection, the present study aimed to evaluate the consequences of induced DM and S. cerevisiae BG on Leishmania amazonensis infection in experimental models. C57BL/6 mice and bone marrow derived macrophages (BMDMs) from conventional and diabetic C57BL/6 mice were used for the experiments. The induction of DM was through administration of streptozotocin (STZ). The animals were infected by L. amazonensis in each ear. It was performed histopathological analysis of the pancreas. Cytokines were evaluated by ELISA. The accumulation of nitrite (NO2) was evaluated using the Griess reagent. The production of reactive oxygen species (ROS) was also evaluated. Animals treated with STZ showed a significant increase in glycemia, in addition to a significant reduction of islets of Langerhans, compared to animals treated with only citrate buffer. The BMDMs of diabetic mice were more susceptible to infection by L. amazonensis and were not able to control parasite multiplication at 48 and 72 hours post infection, thus presenting a higher rate of infection. The presence of DM increased susceptibility to L. amazonensis infection, as diabetic animals were unable to control the parasite load on the lesions in the fourth week of infection, which was significantly higher when compared to conventional mice. About S. cerevisiae BG, this was effective in controlling the parasitic load of macrophages derived from conventional and diabetic mice, reducing the infection rate in both macrophages. Thus, the results suggest that the presence of diabetes mellitus negatively influences L. amazonensis infection and may increase the susceptibility to this infection, in addition, BG was effective in reducing the parasitic burden of BMDMs of conventional and diabetic mice